2011
DOI: 10.3390/molecules17010015
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis of Supercritical Carbon Dioxide and Compressed Propane Extracts from Piper amalago L. with Antileishmanial Activity

Abstract: Piper amalago L. leaves were extracted with supercritical carbon dioxide and compressed propane under different conditions, and with chloroform by the conventional maceration method. These methods were compared for the pyrrolidine alkaloid content. Supercritical carbon dioxide (SFE-CO2) at 313 K and 12.55 MPa showed the highest selectivity for the main compound (600.53 mg/g of extract). A gradient high-performance liquid chromatography (HPLC) method was developed and validated to quantify the alkaloid N-[7-(3′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 56 publications
(68 reference statements)
0
15
0
1
Order By: Relevance
“…The isolation of the alkaloid N-[7-(3′,4′-methylenedioxyphenyl)-2(Z),4(Z)-heptadienoyl]pyrrolidine (compound 1 ) from P. amalago L. leaves and its spectral data were described in a previous study [12]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The isolation of the alkaloid N-[7-(3′,4′-methylenedioxyphenyl)-2(Z),4(Z)-heptadienoyl]pyrrolidine (compound 1 ) from P. amalago L. leaves and its spectral data were described in a previous study [12]. …”
Section: Methodsmentioning
confidence: 99%
“…The infusions of the roots are used as diuretic and against renal stones [5]. Pharmacological investigations have also shown that the extracts from P. amalago leaves present anti-inflammatory [7], anxiogenic [8], diuretic, natriuretic, antilithiatic [9], healing [10], schistosomicidal [11], and antileishmanial activities [12]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Além dos significativos rendimentos observados neste tipo de extração Gonçalves et al, 2013;Lemos et al, 2012), uma grande vantagem dessa tecnologia é a produção de um princípio ativo livre de solventes residuais. Na literatura especializada são vários os trabalhos que reportam a utilização de gases (CO 2 , propano e etileno) a altas pressões na extração de óleos e princípios ativos de oleaginosas (Carrara et al, 2011;Gonçalves et al, 2013;Jesus et al, 2013). Diante da possibilidade de utilização de fluidos supercríticos na extração da cumarina de diversas fontes vegetais, torna-se de extrema importância o estudo da solubilidade deste princípio ativo em fluidos supercríticos, visando assim, a determinação das condições ótimas de extração da cumarina.…”
Section: Introductionunclassified